Diurnal Variations in Upper and Lower Body Power in Adolescent Volleyball Players: Exploring Time-of-Day Effects on Performance - Nebojša Trajković; Vladan Milić; Tomislav Đurković; Tomica Rešetar; Georgiy Korobeynikov (Sports)
Background/Objectives: This study aims to investigate the daily variations in upper and lower body power performance in adolescent volleyball players. Methods: The sample consisted of 50 young male volleyball players (14.12 ± 0.8 years), actively involved in regular training and competition. Players were tested for vertical jump tests and medicine ball throws twice, once in the morning (8:00–9:30 h) and once in the evening (18:00–19:30 h). Results: Significant differences (p < 0.05; ES = 0.35–0.42) in vertical jump were observed when comparing the morning and evening performance except for counter movement jump with arm swing, where there were no significant differences (p = 0.21). The results for the upper body power tests revealed a significant difference only in the standing medicine ball throw (p = 0.05; ES = 0.35). There were no significant differences in lying and seated medicine ball throw (p > 0.05). Conclusions: This study demonstrated that lower body power, manifested in vertical jump performance, was significantly better in the evening compared to the morning. For upper body assessments, the standing medicine ball throw appears more reflective of volleyball-specific movements, while the lying and sitting throw may be less applicable. These findings suggest that volleyball training and testing, especially for leg power, may be more effective later in the day, while upper body performance appears less affected by time.